Thinking caps for everyone?The role of neuro-enhancement by non-invasive brain stimulation in neuroscience and beyond - Felix eDuecker; Tom Alexander de Graaf; Alexander T Sack (Frontiers in Systems Neuroscience, 2014)
Neuro-enhancement by non-invasive brain stimulation (NIBS) has recently made considerable progress, triggering discussions regarding future applications to enhance human performance. We show that neuroscientific research does not aim at improving brain functions per se. Instead, neuro-enhancement is a research tool that has great potential to reveal the neural mechanisms underlying perception, cognition, and behavior. We provide instructive examples that showcase the relevance of neuro-enhancement by NIBS in neuroscience. Importantly, we argue that the scientific value of neuro-enhancement critically depends on our understanding of why enhancing effects occur. This is in contrast to applications of neuro-enhancement in other domains, where such knowledge may not be required. We conclude that neuro-enhancement as a therapeutic tool or in healthy people outside of neuroscience should be kept conceptually distinct, as these are separate domains with entirely different motives for enhancing human performance. Consequently, the underlying principles that justify the application of NIBS will be different in each domain and arguments for or against neuro-enhancement in one domain do not necessarily generalize to other domains.